A review of the optimization of thyroid function, thrombophilia, immunity and uterine milieu: OPTIMUM treatment strategy for recurrent implantation failure and recurrent pregnancy loss - Keiji Kuroda (Reproductive Medicine and Biology)
Abstract Background Aside from embryonic factors, various factors can intricately interfere with embryo implantation and maintenance of pregnancy, causing recurrent implantation failure (RIF) or recurrent pregnancy loss (RPL). This review focuses the optimization of thyroid function, thrombophilia, immunity, and uterine milieu (OPTIMUM) treatment strategy on RIF and RPL. Methods Three studies employing the OPTIMUM treatment strategy for patients with RIF and/or RPL were reviewed. Results The OPTIMUM improved pregnancy rates in women with RIF aged <40 years. Among advanced age women, however, no significant differences in pregnancy rates were observed between the control, OPTIMUM, and preimplantation genetic testing for aneuploidy (PGT‐A) groups, although pregnancy rates were highest after OPTIMUM + PGT‐A. The OPTIMUM reduced miscarriage rates in women with RPL aged <40 years. Among advanced age women, PGT‐A, but not the OPTIMUM, contributed to miscarriage prevention. Factors predicting pregnancy success in women with RIF who received the OPTIMUM included thrombophilia and young age. Risk factors for an unsuccessful live birth among women with RPL who received the OPTIMUM included advanced age, infertility, diminished ovarian reserve, and non‐ART treatment. Conclusions The OPTIMUM can improve pregnancy outcomes in women with RIF/RPL, except for advanced age women with embryonic factor‐induced reproductive failure.